Usare strumenti empirici per risolvere problemi: indagine nella scuola secondaria - Giorgio Asquini; Francesca Marano (LED Edizioni Universitarie, 2016)
The paper presents a deepening of survey problem solving and geographic skills. How to evaluate the competence in the three years of lower secondary school. A second survey was also conducted, after the main investigation with the same tools, in upper secondary school (10th grade), then the data of the two populations are comparable. The deepening aims to investigate the relationship between the use of empirical tools to measure distances on maps and performance in problem solving. The problem solving model used by OECD-PISA is presented, also in relation to its potential educational applications. The analysis of the data confirms a positive correlation between the use of tools and performance for students of lower secondary school and no gender differences. The results for upper secondary school is more complex: the use of some tools does not affect the performance; there are gender differences in performance by the number of tools used.